EFEKTIVITAS MEDIA PEMBELAJARAN INTERAKTIF TERHADAP PEMAHAMAN KONSEP IPA PADA SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - T, Natasya; Wiwik Kurniyati; Erwin Efendi Hutagalung; Ayatullah Muhammadin Al Fath (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of elementary school students’ understanding of science concepts due to the dominance of conventional teaching methods and the limited use of interactive media in the classroom. The study aims to analyze and synthesize the effectiveness of interactive learning media in improving the understanding of science concepts through a Systematic Literature Review (SLR) approach. The research method followed the PRISMA guidelines and the SPAR-4-SLR framework, with data sources from Google Scholar spanning the years 2022–2026, resulting in 10 articles meeting the inclusion criteria. The results indicate that all studies consistently reported a significant improvement in science concept understanding, evidenced by increases in pretest-posttest scores, statistical test results, and media usability ratings. Media with high interactivity and visualization, such as augmented reality, interactive multimedia, and animated videos, demonstrated optimal effectiveness. Additionally, the effectiveness of the media was influenced by design quality, content appropriateness, and teacher competence. Thus, interactive learning media have proven effective when appropriately integrated into instruction.